Microbubbles Stabilized by Protein Shell: From Pioneering Ultrasound Contrast Agents to Advanced Theranostic Systems - Polina G. Rudakovskaya; Roman A. Barmin; Pavel S. Kuzmin; Elena P. Fedotkina; Alexander N. Sencha; Dmitry A. Gorin (MDPI AG, 2022)
Ultrasound is a widely-used imaging modality in clinics as a low-cost, non-invasive, non-radiative procedure allowing therapists faster decision-making. Microbubbles have been used as ultrasound contrast agents for decades, while recent attention has been attracted to consider them as stimuli-responsive drug delivery systems. Pioneering microbubbles were Albunex with a protein shell composed of human serum albumin, which entered clinical practice in 1993. However, current research expanded the set of proteins for a microbubble shell beyond albumin and applications of protein microbubbles beyond ultrasound imaging. Hence, this review summarizes all-known protein microbubbles over decades with a critical evaluation of formulations and applications to optimize the safety (low toxicity and high biocompatibility) as well as imaging efficiency. We provide a comprehensive overview of (1) proteins involved in microbubble formulation, (2) peculiarities of preparation of protein stabilized microbubbles with consideration of large-scale production, (3) key chemical factors of stabilization and functionalization of protein-shelled microbubbles, and (4) biomedical applications beyond ultrasound imaging (multimodal imaging, drug/gene delivery with attention to anticancer treatment, antibacterial activity, biosensing). Presented critical evaluation of the current state-of-the-art for protein microbubbles should focus the field on relevant strategies in microbubble formulation and application for short-term clinical translation. Thus, a protein bubble-based platform is very perspective for theranostic application in clinics.